Potret Sosiologis Hukum Islam di Indonesia - Sunaryo, Agus (Fakultas Syariah IAIN Purwokerto, 2009)
The ability of Islamic law in solving society problems performs a unique creature as the model of Islamic law in Indonesia. Some processes which have proved its existence among the pluralism in Indonesia can be analyzed socially and historically.